PEMELIHARAAN BERKALA JALAN KABUPATEN DINAS PEKERJAAN UMUM KABUPATEN KULON PROGO - , TANARIA WAU ([Yogyakarta] : Universitas Gadjah Mada, 2014)
The road network is a basic infrastructure for the fulfillment of human needs in improving quality of life. In accordance with the government's efforts in development / management of road network, Department of Public Worksin KulonProgo Regency, through its Highways Sector, has a mission to develop a road system through periodic maintenance of district roads. The goal is to maintain a regular maintenance of road conditions remain steady consistence with the level of service and to achievethe predetermined design life. The works of periodic maintenance upon Mandung Road, Adhyaksa Road, and Pengasih Ring Road include resurfacing (overlay) with Laston Layer Aus (ACWC) construction management. To determine the thickness of the overlay, it is required the Daily Traffic Plan Data (LHR). Mobilizations that are needed such as: mobilization of personnel (labor), tools mobilization (Dump Trucks, Asphalt Finishers, Asphalt Sprayer, Tandem Roller, Pneumatic Tire Roller, Air Compressor, etc.), as well as the mobilization of material (hot mix), which are transported from AMP (Asphalt Mixing Plant). Field supervision is indispensable for the smooth execution of the work, especially supervision from the Highways Sector of Department of Public Works in Kulon Progo. Under the plan, the thick overlay for Road Mandung is 5.3 cm